Effect of optical fiber type and absorption medium on the endovenous laser ablation mechanism. (19th September 2017) - Ignatieva, N Yu; Zakharkina, O L; Mazayshvili, C V; Bagratashvili, V N; Lunin, V V
Abstract: Our experimental investigation was aimed at revealing the mechanism behind the action of laser radiation on venous wall under endovenous laser ablation conditions. We determined the critical laser power P cr at which the objective effect of complete denaturation of the vascular tissue collagen was attained for two types of optical fiber in the presence and absence of blood cells. We demonstrated that for the radial optical fiber the presence of blood cells had no effect on the magnitude of P cr, which came to 4.3 ± 0.1 and 5.6 ± 01 W for 1.56 and 1.47 µ m lasers, respectively. For the bare fiber and 1.56 µ m laser, P cr increased up to 5.2 ± 0.2 W in a blood-filled vessel and up to 7.1 ± 0.2 W when the blood was replaced by a sodium chloride solution. Our data show that the heating and degradation of insufficient veins go on more effectively when the tissue is heated by laser radiation directly absorbed therein, rather than the red-hot carbonized optical fiber tip.